Development and Validation of a Scale to Clinically Assess Overall Hair and Scalp Condition – A Pilot Study (Advancements in Homeopathic Research, 2024)
Background: Existing scales for Alopecia measures  severity and stages, all of which are made for  individual types, none of the existed ones can be  applied to all types and no one focuses on the clinical  symptoms which patient addresses while case taking  or can be used to assess the clinical outcomes.  So, a scale was developed on the basis of existing  literatures which can assess the clinical outcomes and  can be apply for all types of alopecia. Objective: To develop alopecia scoring scale to  clinically assess overall hair and scalp condition  based on compilation of existing literature and to test  the reliability and validity of alopecia scoring scale. Material & Methodology: Alopecia scoring scale  was derived after thorough literature review. A pilot  study was conducted on 30 patients who are clinically  diagnosed with alopecia in July 2021 at Swasthya  Kalyan Homoeopathic Medical College & Research  Centre, Sitapura, Jaipur. Result: The internal consistency of scale were  estimated by Cronbach Alpha Coefficient which was  found to be generally satisfactory. The Cronbach  Alpha reliability coefficient 0.82 which suggests  it was found to be reliable. Pearson’s Co-relation  Coefficient obtained value is > 0.7 which is greater  than critical value of 0.361 at df 28 and is highly  significant, so it is a valid scale. Conclusion: The Alopecia Scoring Scale is the  valid and reliable tool to clinically access all types  of Alopecia patients. It might serve as a useful tool  to monitor disease status over time, and to guide  treatment decisions.
Keywords: Alopecia Scoring Scale; Cronbach’s alpha coefficient; Pearson’s co-relation coefficient; Reliability; Validity